Prevalence, radiographic resolution and outcomes of slab fractures of the third and central tarsal bones in juvenile Thoroughbred horses. Issue 4 (27th March 2019) - Steel, CM; Collins, VL; Hance, SR; Adkins, AR; Hitchens, PL
Abstract : Background: Veterinarians are required to interpret the significance of radiographic findings for sale, soundness and future racing performance of weanling and yearling Thoroughbreds. We investigated the prevalence and radiographic appearance of slab fractures of the third (T3) and central tarsal (Tc) bones. Methods: Weanling and yearling horses with complete or incomplete T3 or Tc fracture were identified by searching a database of radiographs. The prevalence and radiographic appearance at initial diagnosis and after continued pasture turnout, as well as prognosis for racing, of fractures of T3 and Tc were determined. Results: Fractures were identified in 186 tarsi (184 T3 fracture only, 1 Tc fracture only, 1 Tc and T3 fracture) of 157 horses (126 unilateral T3, 29 bilateral T3, 1 contralateral Tc and T3, 1 unilateral Tc and T3) from 7676 examinations. The prevalence of T3 and Tc fractures was 2.40 (95% CI 2.07, 2.76) and 0.04 (95% CI 0.01, 0.11) per 100 radiographic examinations respectively. Fractures were identified on the D556–65°MPlLO view and occurred by survey examination at 11.1 ± 1.3 months in 85.7% horses. At initial diagnosis, 84.3% of T3 fractures appeared incomplete and involved the distal articular surface. Fracture score improved (P < 0.001), and dorsal modelling (P < 0.001) and osteoarthritis score increased in the distal intertarsal joint (P < 0.001), but not the tarsometatarsal joint, between survey and repository examinations. Fractures healed by repository examination in 71.9% of tarsi if there was > 6 months between examinations. There was no difference in sale price, and horses with T3 fractures had fewer trials when 2 and 3 years old (P = 0.023), yet no difference in other parameters of racing success when 2 or 3 years old compared with controls. Conclusion: Tarsal slab fractures can occur in juvenile Thoroughbreds and most heal with continued pasture turnout of > 6 months. Further investigation is required to determine risk factors and before making firm conclusions regarding the optimal management, prognosis for racing and long‐term soundness.